PENGEMBANGAN MEDIA NUTSPINBOOK SEBAGAI EDUKASI GIZI SEIMBANG PENINGKAT IMUNITAS UPAYA PENCEGAHAN COVID-19 (Jurnal Kesehatan Siliwangi, 2021)
During the pandemic, food intake must still pay attention to a balanced nutritional menu because it plays a very important role in increasing the body's immunity which can prevent COVID-19 against the body, especially among teenagers. The development of media as a balanced nutrition information enhancer is needed to increase the variety of media among teenagers. The purpose of the research were to: 1) Find out the development of NUTSPINBOOKmedia (Nutrition Spiral Notebook) as a Balanced Nutrition Education to Improve Immunity Efforts to Prevent COVID-19 in Class X Students of SMAN 1 Klari in 2021, 2) Determine the feasibility of NUTSPINBOOK media (Nutrition Spiral Notebook) as Education. Balanced Nutrition Enhancing Immunity Efforts to Prevent COVID-19 in Class X Students of SMAN 1 Klari 2021. This type of research is research and development with a 4D model. The number of samples is 21 students using purposive sampling technique. The results showed that the feasibility of the material was 94.8% categorized as very valid, not revised, the feasibility of the final revised media was 100% categorized as very valid, not revised and the small group test got an average total score of 95.5 with an average percentage a total of 91% categorized as very valid, not revised.